Effect of Panax notoginseng Saponins on Focal Cerebral Ischemia-Reperfusion in Rat Models: A Meta-Analysis - Sun, Tao; Wang, Ping; Deng, Ting; Tao, Xingbao; Li, Bin; Xu, Ying (Frontiers in Pharmacology, 2021)
With the increase in the aging population, the high mortality and disability rates caused by ischemic stroke are some of the major problems facing the world, and they dramatically burden the society. Panax notoginseng (Burk) F. H. Chen, a traditional Chinese medicine, is commonly used for promoting blood circulation and removing blood stasis, and its main bioactive components are Panax notoginseng saponins (PNS). Therefore, we performed a meta-analysis on focal cerebral ischemia-reperfusion (I/R) animal models established with middle cerebral artery occlusion (MCAO) surgery to evaluate the therapeutic effect of PNS. We systematically searched the reports of PNS in MCAO animal experiments in seven databases. We assessed the study quality using two literature quality evaluation criteria, evaluated the efficacy of PNS treatment based on the outcomes of the neurological deficit score (NDS), cerebral infarct volume (CIV) and biochemical indicators via a random/fixed-effects model, and performed a subgroup analysis utilizing ischemia duration, drug dosage, intervention time and administration duration. We also compared the efficacy of PNS with positive control drugs or combination treatment. As a result, we selected 14 eligible studies from the 3,581 searched publications based on the predefined exclusion-inclusion criteria. PNS were significantly associated with reduced NDS, reduced CIV and inhibited release of the inflammatory factors IL-1β and TNF-α in the focal MCAO rat models. The PNS combination therapy outperformed the PNS alone. In addition, ischemia time, drug dosage, intervention time, and administration duration in the rat models all had significant effects on the efficacy of PNS. Although more high-quality studies are needed to further determine the clinical efficacy and guiding parameters of PNS, our results also confirmed that PNS significantly relieves the focal cerebral I/R in rat models. In the animal trials, it was suggested that an early intervention had significant efficacy with PNS alone or PNS combination treatment at dosage lower than 25 mg/kg or 100-150 mg/kg for four days or longer. These findings further guide the therapeutic strategy for clinical cerebral ischemic stroke.